Upaya guru dalam mengatasi penggunaan bahasa daerah pada mata pelajaran bahasa indonesia di sekola MIS Jadil Maad Aloindonu - Lutfia Tika Dewi Ahmad; Ismail Tamal Biat; Mahmud Abdullah Noho (STKIP Muhammadiyah Kalabahi, 2026)
Teachers' efforts in overcoming the use of regional languages ​​in the Indonesian Language subject for grade III at MIS Zadil Maad Aloindonu School. The purpose of this study was to determine the efforts of teachers in overcoming the use of regional languages ​​in the Indonesian Language subject for grade III at MIS Zadil Maad Aloindonu. Teachers' efforts in overcoming the use of regional languages ​​in the Indonesian Language subject for grade III at MIS Zadil Maad Aloindonu and to find out what inhibiting factors the school faced in overcoming the use of regional languages ​​in grade III at MIS Zadil Maad Aloindonu. Using a descriptive qualitative method. The subjects of this study were the principal, Indonesian Language teachers and students. Data collection techniques used were observation, interviews, and documentation with analysis techniques, namely data reduction, data display. The verbal rules made by the principal of MIS Zadil Maad Aloindonu reprimand students and teachers if they always use Indonesian at school or in learning, the principal also began to implement the use of Indonesian in the school environment, especially in learning and giving authority to each teacher and each homeroom teacher to make rules and punishments for students who use regional languages ​​too much at school or in learning